Asian gangs in the United States: the current state of the research literature - Tsunokai, Glenn T. (Crime, law and social change, 2002)
Since the late 1980s, criminologists have been interested in analyzing Asian gangs. Despite the rather sharp increase in books and articles published on the subject in the1990s, there appears to exist no consensus on the nature and etiology of Asian gangs. This paper describes the current state of research on Asian gangs and assesses whether or not there is a dominant criminological theory on their cause. It compares and contrasts African American and Asian gangs, and closes with research and policy recommendations.